Emotional and behavioral problems and psychosocial skills in adolescents in residential care - Campos, Joana (2019)
Research suggests that mental health problems in adolescents in residential care (RC) are more prevalent than for youth in the community, and that psychosocial competencies are protective factors of mental health. This study compared adolescents in RC in Portugal, with a Portuguese community sample on the incidence of mental health problems and psychosocial skills, explored gender differences and the relationships between mental health problems and psychosocial competencies. Four hundred and forty-three adolescents in RC participated. Results showed that the RC adolescents had higher levels of mental health problems lower academic achievement, a poorer social support network, but were more involved in sports and hobbies, household chores than the adolescents in the normative sample. Gender differences were observed. Psychosocial skills were negatively correlated with mental health problems. These findings indicate an urgent need in Portugal for early screening of mental health problems and socio-cognitive interventions for youth in RC.